Genotype-Phenotype Correlation of G6PD Mutations among Central Thai Children with G6PD Deficiency - Boonchai Boonyawat; Tim Phetthong; Nithipun Suksumek; Chanchai Traivaree (Anemia)
Background. Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common X-linked inherited erythroenzymopathy in Thailand. The clinical and hematological manifestations of G6PD deficiency are variable. Objective. This study aimed to characterize the genotype-phenotype correlation of G6PD mutations in Thai pediatric patients who were followed-up in Phramongkutklao Hospital, a tertiary center in central Thailand. Material and Method. A total of 102 children including 73 males (71.6%) and 29 females (28.4%) were included in our study. Mutation analysis was performed by direct DNA sequencing of all coding exons of the G6PD gene. Ninety-one patients (89.2%) were presented with neonatal hyperbilirubinemia and 11 patients (10.8%) were presented with acute hemolytic anemia beyond the neonatal period. Results. Molecular analysis of the G6PD gene in 102 G6PD-deficient Thai children identified 12 different mutations. G6PD Viangchan (871G > A) and G6PD Canton (1376G > T) were the first (46.2%) and the second (15.4%) most common identified mutations among both male and female G6PD-deficient individuals, respectively. All affected males were hemizygous for G6PD mutations and had an average G6PD level of 16.7 ± 11.5 (3–76) IU/ml.RBC. Majority of female patients (27 in 29, 93.1%) were heterozygous for G6PD mutations and had an average G6PD level of 133.6 ± 43.4 (9–195) IU/ml.RBC. Two female patients (6.9%) were either homozygous or compound heterozygous for the mutations and had G6PD level in the affected male range (35 and 10 IU/ml.RBC). Only 1 in 27 heterozygous females (3.7%) had G6PD level in the affected male range (9 IU/ml.RBC) which is possibly explained by nonrandom X-chromosome inactivation. The correlation of genotypes, G6PD levels, and clinical phenotypes was not demonstrated in our study in which all of the included G6PD-deficient patients were presented with neonatal hyperbilirubinemia and acute hemolytic anemia, since the genotype-phenotype correlation is normally demonstrated in chronic nonspherocytic hemolytic anemia (CNSHA) G6PD-deficient individuals. Conclusion. This study characterizes the molecular heterogeneity of G6PD variants causing G6PD deficiency in Thai children. Our study demonstrated the efficiency of direct DNA sequencing which can identify 12 missense mutations in Thai children.